161 Greening vacant properties: an innovative approach to youth violence prevention. (19th September 2017) - Zimmerman, Marc; Morrel-Samuels, Susan; Reischl, Thomas; Pruett, Natalie; Merrill, Liberty; Hohl, Bernadette
Abstract : Statement of Purpose: The purpose of this symposium is to provide an in-depth view of the innovative research being conducting by the MI Youth Violence Prevention Centre (MI-YVPC) examining the effects of improving vacant properties on youth crime and injury. Description of Topic: Although youth violence has been in relatively steady decline for the last few decades, in some urban centres violence prevention remains an urgent priority. Communities that historically depended on their industrial bases now experience high rates of depopulation, unemployment and distress. Throughout many of these cities, abandoned, blighted properties are a constant visual reminder of these problems. Lack of jobs and quality education options for youth have resulted in elevated rates of violence. Moreover, violent crime incidents often occur near neglected or blighted properties, which appear to be opportune places for illegal activities. The MI-YVPC has undertaken innovative research to study the effects of improving vacant and neglected properties on violent crime, intentional injuries, neighbourhood perceptions, and adjacent property conditions in Flint, MI and Youngstown, OH. This approach includes partnering with stakeholders from multiple sectors (academic, community and municipal), and applying rigorous study design with varied methodologies using spatial, systematic observation, survey and administrative data.Previous research suggests that greening blighted community spaces can have significant effects on public health outcomes because it makes structural changes to places and is readily scalable to cover large populations. These novel approaches to violence prevention are relatively straightforward, inexpensive, and sustainable. Interest in health and safety programs that directly change the places where people live, work, and play has grown over the past decade. Structural interventions, including place-based programs like greening, have the potential to become truly transformational for the health and safety of large populations because they can influence more people for longer periods of time than those that focus on individual behaviour change. MI-YVPC is building on this emerging body of research. Our application of Busy Streets and Empowerment Theories provide the conceptual foundation for testing a participatory greening strategy. We incorporated three conditions in our mixed random experimental design: 1) community and youth-engaged greening; 2) professionally implemented greening; and 3) no maintenance. This design tests the notion that community empowerment is a vital component for creating effective neighbourhood changes to prevent youth violence. Format: The symposium includes four components: 1) overview of MI-YVPC research design and methods; 2) description of the greening interventions being conducted in Flint, MI and Youngstown, OH; 3) in-depth discussion of the spatial methods for the study and their application; 4) results from the first season of data collection on property conditions, resident perceptions and behaviours, and social observations. Dr. Deborah Houry, NCIPC Director, will comment on the presentations and facilitate discussion. The presenters bring varied perspectives and expertise to the symposium. They include community development practitioners and researchers from diverse disciplines, (e.g., urban planning, psychology, epidemiology). The presentations will be interactive and incorporate images and graphics to enliven the content of the talks. We will encourage active discussion and engagement.